MxMPK4‐1 phosphorylates NADPH oxidase to trigger the MxMPK6‐2‐MxbHLH104 pathway mediated Fe deficiency responses in apple. (6th July 2022) - Zhai, Longmei; Sun, Qiran; Gao, Min; Cheng, Xinxin; Liao, Xiaojun; Wu, Ting; Zhang, Xinzhong; Xu, Xuefeng; Wang, Yi; Han, Zhenhai
Abstract: Iron (Fe) deficiency is a nutritional stress in plants that commonly occurs in alkaline and calcareous soils. Mitogen‐activated protein kinases (MPKs), the terminal player of MAPK cascade, are involved in distinct physiological processes. Once plants suffer from Fe deficiency stress, the mechanism of MPK function remains unclear owing to limited study on the MPK networks including substrate proteins and downstream pathways. Here, the MAP kinase MPK4‐1 was induced in roots of Fe efficient apple rootstock Malus xiaojinensis but not in Fe inefficient rootstock Malus baccata under Fe deficiency conditions. Overexpression of MxMPK4‐1 in apple calli and apple roots enhanced the responses to Fe deficiency. We found that MxMPK4‐1 interacted with NADPH oxidases (NOX)—respiratory burst oxidase homologs MxRBOHD1 and MxRBOHD2, which positively regulated responses to Fe deficiency. Moreover, MxMPK4‐1 phosphorylated the C terminus of MxRBOHD2 at Ser797 and Ser906 and positively and negatively regulated NOX activity through these phospho‐sites, respectively. When compared with apple calli that overexpressed MxRBOHD2, the coexpression of MxMPK4‐1 and MxRBOHD2 prominently enhanced the Fe deficiency responses. We also demonstrated that hydrogen peroxide derived from MxMPK4‐1‐MxRBOHD2 regulated the MxMPK6‐2‐MxbHLH104 pathway, illuminating a systematic network that involves different MPK proteins in M. xiaojinensis under Fe deficiency stress.